Female representation in Colombia a historical analysis (1962-2014) (2018)
Mónica Pachón and Santiago E. Lacouture examine the case of Colombia and show that women’s representation has been low and remains low in most arenas of representation and across national and subnational levels of government. The authors identify institutions and the highly personalized Colombian political context as the primary reasons for this. Despite the fact that Colombia was an electoral democracy through almost all of the twentieth century, it was one of the last countries in the region to grant women political rights. Still, even given women’s small numbers, they do bring women’s issues to the political arena. Pachón and Lacoutre show that women are more likely to sponsor bills on women-focused topics, which may ultimately lead to greater substantive representation of women in Colombia. © Oxford University Press 2018.